Inovasi Pendidikan Kristen untuk Kesehatan Spiritual pada Anak Generasi Alpha - Harefa, Heppy Agustina; Santosa, Monica (P3M STT Kristus Alfa Omega, 2024)
The Alpha generation faces challenges in Christian religious education (CHE) due to their engagement with technology. This research aims to explore the application of modern technologies, such as neurofeedback, holograms, augmented reality (AR), and blockchain, in religious learning. The research method utilizes literature to assess the effectiveness of the technologies in enhancing student engagement. The results show that these technologies not only enrich the learning experience by presenting material interactively, but also help students manage emotions and record progress transparently. With this innovative approach, Christian religious education can become more relevant and engaging for the Alpha generation in the digital age.